Pengaruh Motivasi Hedonisme dan Korean Wave Terhadap Impulsive Buying dengan Personal Branding Syariah Sebagai Variabel Intervening - Faturrazaq, Ramadhani Aulia; Sukresna, I Made (ITB AAS INDONESIA Surakarta, 2023)
In the last two decades, Korean culture has experienced rapid development and has spread globally to various countries in the world, including Indonesia. The Korean Wave or in Korean usually called hallyu according to (Suh, Cho, & Kwon, 2006) is defined as